CD36 homolog divergence is responsible for the selectivity of carotenoid species migration to the silk gland of the silkworm Bombyx mori - Sakudoh, Takashi (The American Society for Biochemistry and Molecular Biology, 2013)
Dietary carotenoids are absorbed in the intestine and delivered to various tissues by circulating lipoproteins; however, the mechanism underlying selective delivery of different carotenoid species to individual tissues remains elusive. The products of the Yellow cocoon (C) gene and the Flesh (F) gene of the silkworm Bombyx mori determine the selectivity for transport of lutein and β-carotene, respectively, to the silk gland. We previously showed that the C gene encodes Cameo2, a CD36 family member, which is thought to function as a transmembrane lipoprotein receptor. Here, we elucidated the molecular identity of the F gene product by positional cloning, as SCRB15, a paralog of Cameo2 with 26% amino acid identity. In the F mutant, SCRB15 mRNA structure was severely disrupted, due to a 1.4 kb genomic insertion in a coding exon. Transgenic expression of SCRB15 in the middle silk gland using the binary GAL4-UAS expression system enhanced selective β-carotene uptake by the middle silk gland, while transgenic expression of Cameo2 enhanced selective lutein uptake under the same GAL4 driver. Our findings indicate that divergence of genes in the CD36 family determines the selectivity of carotenoid species uptake by silk gland tissue and that CD36-homologous proteins can discriminate among carotenoid species.